Investigating Bioactive-Glass-Infused Gels for Enamel Remineralization: An In Vitro Study - Raszewski, Zbigniew; Chojnacka, Katarzyna; Mikulewicz, Marcin (Journal of functional biomaterials, 2024)
OBJECTIVE: Dental hypersensitivity remains widespread, underscoring the need for materials that can effectively seal dental tubules. This study evaluated the potential of bioactive-glass-infused hydroxyethyl cellulose gels in this context. METHODS: Five gels were synthesized, each containing 20% bioactive glass (specifically, 45S5, S53P4, Biomin F, and Biomin C), with an additional blank gel serving as a control. Subjected to two months of accelerated aging at 37 ± 2 °C, these gels were assessed for key properties: viscosity, water disintegration time, pH level, consistency, adhesion to glass, and element release capability. RESULTS: Across the board, the gels facilitated the release of calcium, phosphate, and silicon ions, raising the pH from 9.00 ± 0.10 to 9.7 ± 0.0-a range conducive to remineralization. Dissolution in water occurred within 30-50 min post-application. Viscosity readings showed variability, with 45S5 reaching 6337 ± 24 mPa/s and Biomin F at 3269 ± 18 mPa/s after two months. Initial adhesion for the blank gel was measured at 0.27 ± 0.04 Pa, increasing to 0.73 ± 0.06 Pa for the others over time. Gels can release elements upon contact with water (Ca- Biomin C 104.8 ± 15.7 mg/L; Na- Biomin F 76.30 ± 11.44 mg/L; P- Biomin C 2.623 ± 0.393 mg/L; Si- 45S5-45.15 ± 6.77mg/L, F- Biomin F- 3.256 ± 0.651mg/L; Cl- Biomin C 135.5 ± 20.3 mg/L after 45 min). CONCLUSIONS: These findings highlight the gels' capacity to kickstart the remineralization process by delivering critical ions needed for enamel layer reconstruction. Further exploration in more dynamic, real-world conditions is recommended to fully ascertain their practical utility.